2013
DOI: 10.1128/jb.02273-12
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Morphogenesis Is Intimately Linked to the Intracellular Redox State

Abstract: Many microbial species form multicellular structures comprising elaborate wrinkles and concentric rings, yet the rules governing their architecture are poorly understood. The opportunistic pathogen Pseudomonas aeruginosa produces phenazines, small molecules that act as alternate electron acceptors to oxygen and nitrate to oxidize the intracellular redox state and that influence biofilm morphogenesis. Here, we show that the depth occupied by cells within colony biofilms correlates well with electron acceptor av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
334
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 281 publications
(355 citation statements)
references
References 43 publications
16
334
1
4
Order By: Relevance
“…More recently, we showed that P. aeruginosa colony wrinkling is a strategy to increase oxygen accessibility (28). We have proposed that phenazines attenuate this mechanism because they act as electron acceptors for cells in anoxic regions of the biofilm and shuttle electrons to the well-aerated regions, allowing cells to balance their internal redox state (28,32,33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we showed that P. aeruginosa colony wrinkling is a strategy to increase oxygen accessibility (28). We have proposed that phenazines attenuate this mechanism because they act as electron acceptors for cells in anoxic regions of the biofilm and shuttle electrons to the well-aerated regions, allowing cells to balance their internal redox state (28,32,33).…”
mentioning
confidence: 99%
“…Colony biofilms that form under these conditions exhibit spatial patterning (Fig. 1A) and environmental sensitivity and constitute an ideal model system for exploring morphology as a metabolic adaptation (28).…”
mentioning
confidence: 99%
“…The advantage for P. aeruginosa is to maintain redox homeostasis, and thus to survive, under anaerobic conditions within the deeper layers of the biofilm when PYO is present (Dietrich et al, 2013). This extracellular electron transfer with oxygen over a distance can be measured quantitatively and in real time by electric current production through the oxidation of reduced PYO at an electrode as the solid-state electron acceptor in a bioelectrochemical system (Rabaey et al, 2005;Venkataraman et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, P. aeruginosa has three high-affinity terminal oxidases and has a preference to respire with oxygen and nitrate rather than to ferment (Madigan et al, 2002;Alvarez-Ortega and Harwood, 2007), albeit it can ferment with arginine (Vander Wauven et al, 1984). Even when oxygen is not present in the deeper layers of the biofilm and respiration becomes unlikely, P. aeruginosa may be able to survive by producing reduced PYO that eventually can react extracellularly with oxygen at the boundaries of the biofilm (Dietrich et al, 2013). Regardless, bacterial fermenters have a much higher substrate turnover rate than respirers because of inefficient carbon usage, allowing fermenters to predominate when fermentable substrates (including the blood sugar glucose or extracellular polysaccharides) are present (Madigan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation